2021
DOI: 10.1111/cas.15086
|View full text |Cite
|
Sign up to set email alerts
|

TH1902, a new docetaxel‐peptide conjugate for the treatment of sortilin‐positive triple‐negative breast cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 67 publications
0
44
0
1
Order By: Relevance
“…In addition, based on the specific binding of peptides to proteins, peptides represent the novel drug conjugates. For example, a peptide-docetaxel-conjugate (TH1902) targeting sortilin exerts anticancer effects in TNBC cells and tumor xenograft models [ 165 ]. A novel analog conjugate (CX-2009, praluzatamab ravtansine) was studied in 22 patients with advanced HR + /HER − BC with the probody drug conjugate (PDC), showing that 9% patients had partial responses and 45% of patients had stable disease [ 166 ].…”
Section: Immunotherapy For Tnbcmentioning
confidence: 99%
“…In addition, based on the specific binding of peptides to proteins, peptides represent the novel drug conjugates. For example, a peptide-docetaxel-conjugate (TH1902) targeting sortilin exerts anticancer effects in TNBC cells and tumor xenograft models [ 165 ]. A novel analog conjugate (CX-2009, praluzatamab ravtansine) was studied in 22 patients with advanced HR + /HER − BC with the probody drug conjugate (PDC), showing that 9% patients had partial responses and 45% of patients had stable disease [ 166 ].…”
Section: Immunotherapy For Tnbcmentioning
confidence: 99%
“…Efficient inhibition of cells exhibiting VM is challenging given the combined lack of specific cell surface biomarkers and functional targeting. Recently, a novel targeted therapy strategy was developed against sortilin (SORT1)-positive ovarian and breast cancers ( 16 , 17 ). As such, tumor suppressive capacities of TH1902, a drug currently tested in a phase 1, open-label first-in-human study in solid cancer (ClinicalTrials.gov Identifier: NCT04706962), were demonstrated against SORT1-positive TNBC xenograft models ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel targeted therapy strategy was developed against sortilin (SORT1)-positive ovarian and breast cancers ( 16 , 17 ). As such, tumor suppressive capacities of TH1902, a drug currently tested in a phase 1, open-label first-in-human study in solid cancer (ClinicalTrials.gov Identifier: NCT04706962), were demonstrated against SORT1-positive TNBC xenograft models ( 17 ). SORT1 is a key scavenging receptor discovered two decades ago as the first member of the small family of vacuolar protein sorting 10 protein domain (Vps10p) ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scientists exploited peptides conjugated with anticancer drugs to eradicate tumor cells. In a study carried out by Annabi et al , it was shown that a novel curcumin-peptide conjugate called TH1901 inhibited cancer cell proliferation in sortilin-positive cancers including ovary (ES2), breast (MD-MB231, HCC-1569, and HCC-1954), skin (SK-MEL-28 and A-375), and colorectal (HT-29) cancers 29 . Two other peptides conjugated to docetaxel (TH1902) and doxorubicin (TH1904) are specifically designed to target sortilin receptor (SORT1).…”
Section: Discussionmentioning
confidence: 99%